Elements of deductive logic - Eagle, A (2008)
A textbook for an 'advanced introductory' logic class (I used it as a textbook for mathematically capable introductory logic students). The book uses the tableau method, and includes standard results up to a proof of the soundness of predicate logic. Its slightly unusual features include a slightly greater emphasis on decidability than is usual, some discussion of philosophical issues, and more obviously, the presentation of a free logic as standard, alongside a classical alternative.